2020
DOI: 10.1177/0300060520917581
|View full text |Cite
|
Sign up to set email alerts
|

Clinical value of matrix metalloproteinase-2 and -9 in ultrasound-guided radiofrequency ablation treatment for papillary thyroid carcinoma

Abstract: Objective This study aimed to investigate serum matrix metalloproteinase (MMP)-2 and MMP-9 levels in patients with papillary thyroid carcinoma (PTC). Methods Forty-one patients with PTC undergoing ultrasound-guided radiofrequency ablation (RFA) and 56 controls were included. Serum MMP-2 and MMP-9 levels were determined by enzyme-linked immunosorbent assay before and after surgery. Potential affecting factors were evaluated by logistic regression analysis. Results Serum MMP-2 and MMP-9 levels were significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Pan et al [31] found that age and calcification were influencing factors for PTC prognosis; however, they did not further explore whether these factors influenced complete ablation zone disappearance after RFA. In our study, we found that aged patients and/or patients who had macrocalcification usually had difficulty in achieving complete ablation zone disappearance in the first year after RFA.…”
Section: Discussionmentioning
confidence: 98%
“…Pan et al [31] found that age and calcification were influencing factors for PTC prognosis; however, they did not further explore whether these factors influenced complete ablation zone disappearance after RFA. In our study, we found that aged patients and/or patients who had macrocalcification usually had difficulty in achieving complete ablation zone disappearance in the first year after RFA.…”
Section: Discussionmentioning
confidence: 98%
“…The serum concentrations of MMP-2 and MMP-9 differ significantly regarding age, presence of microcalcification, irregular shape, diameter or number of cancer foci, and other clinicopathological features mentioned earlier [ 184 ].…”
Section: Extracellular Matrix Degradationmentioning
confidence: 99%
“…Several studies suggest that levels of MMP-2 and MMP-9 in the peripheral blood could be used not only as predictive markers of DTC [ 178 , 179 , 184 ] but also as the efficacy criterion for different treatment methods, e.g., surgery [ 168 ] or minimally invasive procedures, such as Ult RAS ound-guided Radiofrequency Ablation (RFA) [ 184 ]. Serum levels of MMP-2 and MMP-9 could provide valuable references for diagnosing PTC before RFA and information about procedures efficacy.…”
Section: Extracellular Matrix Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overexpression of MMPs in tumor tissue has been reported in many types of solid tumors, including breast, ovary, colorectal, and pancreatic carcinomas, squamous carcinomas of the head and neck, and other carcinomas [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Human thyroid carcinoma tissue has also been reported to express MMP-1, MMP-2, and MMP-9 and these MMPs were localized in tumor cells and/or in the fibroblasts adjacent to or close to the invading tumor cells [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. TIMPs, as inhibitors of MMPs, were initially considered as potential inhibitors of invasion and metastases that could alter the metastatic potential of cancer cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%